2015
DOI: 10.1007/s10384-015-0404-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between the major histocompatibility complex and clinical response to infliximab therapy in patients with Behçet uveitis

Abstract: Although mean change from baseline in the number of ocular attack scores in the HLA A26 and HLA B51 groups seemed to be similar, the HLA-A26 group had a more severe disease course under infliximab therapy for ocular/extraocular involvement. These data suggest that response to infliximab therapy in Japanese patients with BU is partly due to genetic determinants in the HLA complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…HLA-A*26 carriers have been reported to have a higher risk of iridocyclitis and retinochoroiditis, which is more prominent in men. 29 Kuroyanagi et al 41 However, a study evaluating the complete HLA panel and its correlation with clinical findings in an acceptable number of well-characterized BD patients, such as ours, has not yet been performed. We found differences in allelic distribution based on ethnicity, which is supported by ancestry testing in specific populations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…HLA-A*26 carriers have been reported to have a higher risk of iridocyclitis and retinochoroiditis, which is more prominent in men. 29 Kuroyanagi et al 41 However, a study evaluating the complete HLA panel and its correlation with clinical findings in an acceptable number of well-characterized BD patients, such as ours, has not yet been performed. We found differences in allelic distribution based on ethnicity, which is supported by ancestry testing in specific populations.…”
Section: Discussionmentioning
confidence: 91%
“…HLA-A*26 carriers have been reported to have a higher risk of iridocyclitis and retinochoroiditis, which is more prominent in men 29 . Kuroyanagi et al 41 demonstrated an association between HLA-A*26 and the clinical response to infliximab therapy in Japanese patients with BD uveitis and concluded that patients who presented with HLA-A*26:01 had the best visual acuity after treatment. Recently, Su et al 42 identified HLA-A*26 as a new risk allele for uveitis in a Chinese population with BD.…”
Section: Discussionmentioning
confidence: 99%
“…A new generation of biological compounds that inhibit T cell activation such as monoclonal antibodies and recombinant forms of natural inhibitory molecules have emerged (36,37). For example, IFX is validated for the treatment of refractory ocular Behçet's disease (1,38,39). Adalimumab (ADA), which is a recombinant human immunoglobulin G1 monoclonal antibody to TNF-α, has also been validated for the treatment of patients with NIU in the United States and in Japan.…”
Section: Non-infectious Uveitis (Niu) Human Non-infectious Uveitismentioning
confidence: 99%